Book Review: “Muslim Minority-State Relations (Violence, Integration and Policy) The Executive Summary: Robert Mason, First Published 2016 by. Palgrave Macmillan, 2016 - Mustaqilla, Safira (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2017)
The book under the auspices of the modern Muslim world in a tittle â€œMuslim Minority-State Relations: Violence, Integration and Policyâ€, described on the minority Muslim community before the government 11 september, and thereafter. Before the reign of 11 September, the government does not target minority Muslim community with a comprehensive policy that aims to foster multiculturalism, integration and social cohesion. But in the last decade all of has changed.Now Muslims are confronted by the global issue of radicalization, the legitimacy of actors Muslims and Islam to be a challenge to traditional national identity. The issue is more visible in 2015 when the conflict in Syria, and instability in other parts of the Middle East and Africa has sparked a new case of terrorism in Europe carried out by Islamic State of Iraq and the Levant. More than 350,000 migrants were on the border of the EU between January and August 2015, more than the total figure for 2014. Germany alone, expects to receive 800,000 refugees and asylum-seekers in 2015, four times in 2014.That glimpse of the picture presented by Robert Mason about the situation of Muslim minorities in some parts of the western countries and the Middle East. This book consists of eight chapters. Each chapter is summarized well by the writer. each contents highlight about the position of minorities and their involvement in the public sphere. The authors describe a wide range of minority issues from different countries, with several cases of violence and the restrictions experienced by minorities. This book is very helpful, because it contains a variety of information that is current and up to date, about the state of minorities in various countries around the globe. And this book is the first edition in 2016.